1991
DOI: 10.4141/cjas91-023
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of a low protein diet in an attempt to optimize egg mass output

Abstract: Chez la plupart des poules nourries avec les raiions exp6rimentales, la production d'oeufs a diminu6 imm6diatement, ir environ 70%. Aprds le pic de ponte, le poids corporel des poules recevant les rations exp6rimentales est demeure constant ou a diminu6, alors qu'il a augment6 normalement chez les poules t6moins. En outre, I'accroissement de la taille des oeufs a 6t6 comparable, que les poules regoivent les rations exp6rimentales ou t6moin. Lors d'une deuxibme exp6rience effectu6e sur des poules plus Agees, la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 10 publications
0
17
0
3
Order By: Relevance
“…It may have resulted from a reduction in egg weight without any changes in egg production. The negative effect of low protein diets with or without supplemental amino acids on egg mass has also been reported by other authors (Penz and Jensen, 1991;Summers et al, 1991;Keshavarz and Jackson, 1992). In contrast, Harms and Russell (1993) reported similar responses in egg production parameters, including egg mass, when lowprotein diets (15% or 13%) with supplemental Lys, Met, Trp, Arg, Thr, Val, and Ile were compared with high protein (17.6% or 15.5%) diets.…”
Section: Discussionmentioning
confidence: 42%
“…It may have resulted from a reduction in egg weight without any changes in egg production. The negative effect of low protein diets with or without supplemental amino acids on egg mass has also been reported by other authors (Penz and Jensen, 1991;Summers et al, 1991;Keshavarz and Jackson, 1992). In contrast, Harms and Russell (1993) reported similar responses in egg production parameters, including egg mass, when lowprotein diets (15% or 13%) with supplemental Lys, Met, Trp, Arg, Thr, Val, and Ile were compared with high protein (17.6% or 15.5%) diets.…”
Section: Discussionmentioning
confidence: 42%
“…Genetics determine the maximum size to be reached by the egg. As the bird grows older, egg size increases rapidly during the first 4 months of the laying period, then more slowly until a maximum size is reached at 70 to 90 weeks of age (Cowen et al, 1964;Summers et al, 1991;Shalev and Pasternak, 1995;Lokhorst, 1996). The increase in egg weight parallels the increase in average body weight of the flock (Weatherup and Foster, 1980;Adams and Bell, 1998).…”
Section: Introductionmentioning
confidence: 88%
“…An additional practical strategy is to reduce the amount of N that is excreted by the bird as opposed to alleviating the problem after the waste has been produced. This can be done by either adding enzymes to the diet to improve N utilisation (Nahm, 2007), or by reducing the CP content of the diet and supplementing limiting amino acids to reduce the amount of excess N that would otherwise be excreted (Fernandez et al, 1973;Calderon and Jensen, 1990;Penz and Jensen, 1991;Summers et al, 1991;Blair et al, 1999;Liang et al, 2005Liang et al, , 2008Valkonen et al, 2006;Novak et al, 2008). Cromwell and Coffey (1995) and Creswell and Swick (2001) found that the use of dietary synthetic AAs in combination with low CP diets could potentially reduce N excretion by up to 40%.…”
Section: Potential Mitigation Strategiesmentioning
confidence: 97%